Philosophical Thought of Le Thanh Tong - Chinh, Doan; Cu, Luong Minh (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
In the development of Vietnamese history, the period of the 14th - 15th centuries was one of the special periods; Many great thinkers appeared, notably Le Thanh Tong. He is not only a politician and a culturalist but also a thinker, expressed quite uniquely in his views on the world, on perception, on human issues, as well as on human rights issues. Socio-political topics, the most prominent of which are his thoughts and achievements on the organization of the state apparatus, and administrative and legal reform.